2006
DOI: 10.1055/s-2006-951728
|View full text |Cite
|
Sign up to set email alerts
|

Bonabiline A, a Monoterpenoid 3α-Acyloxytropane from the Roots of Bonamia spectabilis showing M3 Receptor Antagonist Activity

Abstract: Two 3alpha-acyloxytropanes with unique monoterpenoic acyl moieties, bonabiline A and its anhydro derivative bonabiline B, have been isolated from the roots of Bonamia spectabilis. Their structures were elucidated by detailed spectroscopic analysis. Due to the structural similarity of bonabiline A to atropine/hyoscyamine, the affinity of both bonabilines to the muscarinic M (3) receptor was studied in the isolated guinea-pig ileum. Bonabiline A (pA (2) 6.65 +/- 0.03) proved to be a more potent antagonist than b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…During our continuous studies on secondary metabolites of the Convolvulaceae, this plant family has been shown to produce a plethora of tropane alkaloids, especially 3-tropanols and their esters (e. g. [1, 2]), as well as some 3,6-disubstituted tropanes [3] or the polyhydroxylated calystegines [4]. This underlines the chemotaxonomic relationship with their sister family Solanaceae where the biosynthetic pathway of tropane alkaloids is well investigated.…”
Section: Introductionmentioning
confidence: 97%
“…During our continuous studies on secondary metabolites of the Convolvulaceae, this plant family has been shown to produce a plethora of tropane alkaloids, especially 3-tropanols and their esters (e. g. [1, 2]), as well as some 3,6-disubstituted tropanes [3] or the polyhydroxylated calystegines [4]. This underlines the chemotaxonomic relationship with their sister family Solanaceae where the biosynthetic pathway of tropane alkaloids is well investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Another similar genus from the Convolvulaceae family, Bonamia (not to be confused with the parasite) has been shown in the literature to produce monoterpenes and lignans [5]. The isolation, structure elucidation, and antiproliferative properties of 1 are reported herein.…”
mentioning
confidence: 96%